Assessing the significance of rate and time pulse spraying in top spray granulation of urea fertilizer using Taguchi method - Omar, Rostam; Dimin @ Mohd Amin, Mohd Fairuz; Subramonian, Sivarao; Mohamad Yatim, Norazlina; Shaaban, Azizah; Luqman, H. H.; Lau, Kok Keong; Said, Md Radzai; Mohamad, Norhidayah (Trans Tech Publications Ltd., 2015)
Studies in urea granulation process using Top Spray Fluidized Bed Granulator (TSFBG) is still limited and requires in-depth research about the effectiveness and influence of droplets to the formation of urea granule (UG). Rate and time interval of spraying technique (Pulse) significantly influence the physical properties of urea granules. Cassava starch dissolves in water was selected as the binder released at various time interval to observe impact of spray droplet on UG size formation. Using Taguchi Method, the study had identified three leading factors contributed to the formation of droplet size namely volume of binder (VOB), time pulse of spraying (TPS) and spraying rate (SR). These factors were then evaluated in terms of the influence on response as signal-to-noise analysis (S/N ratios) from Taguchi to validate UG size in range 2 mm to 4 mm from screening process with respect to the actual experimental data. These results were useful for future experiment reference to determine pressure drop and surface contact during interaction between droplet and urea powder particles using TSFBG to obtain uniform UG size and smooth surface layer with reasonable hardness.